Analisis Perilaku Konsumen Terhadap Keputusan Pembelian Tanaman Hias Aglaonema (Study Kasus Desa Bangun Sari) Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Ricky Hotri Parlindungan Sihotang; Juliana Simbolon; Lyndon Parulian Nainggolan (JURNAL REGIONOMIC, 2022)
Bangun Sari Village, which is located in the Tanjng Morawa sub-district, is a shopping center for ornamental plants, especially aglaonema ornamental plants, to be precise, one of the largest ornamental plant shopping centers in Deli Serdang Regency. The analysis used in this study is Multiple Linear Regression. This research was conducted in Bangun Sari Village, this study involved consumers of Aglaonema ornamental plants, the results of this study were that there were positive factors that caused the purchase decision of Aglaonema ornamental plants by taking a sample of 50 respondents who were involved in purchasing ornamental plants in Bangun Sari Village. Tanjung Morawa District, Deli Serdang Regency.